Barriers to Corporate Social Responsibility: the perceptions of a leading non-governmental organization - Delmonico, Diego Valerio de Godoy; Santos, Hugo Henrique dos; Luiz, Octaviano Rojas; Luiz, João Victor Rojas; Bezerra, Bárbara Stolte; Battistelle, Rosane Aparecida Gomes (Revista Gestão da Produção Operações e Sistemas, 2020)
Purpose – This study aims to identify the main barriers to develop Corporate Social Responsibility (CSR) from the viewpoint of a leading Non-governmental Organization (NGO). The proposed methodology evaluates the importance attached to different classes of barriers to CSR from the privileged perspective of a Brazilian NGO. Theoretical framework – This study was based on the current theory of barriers to CSR initiatives and multicriteria decision making. Design/methodology/approach – The Analytic Hierarchy Process (AHP) method was used to assess and prioritize barriers to CSR through expert opinion. The ranking of stability was tested through a sensitivity analysis of the assigned weights. Findings – The results indicate that the main barrier is a lack of commitment of senior management. By contrast, the least determining barriers were a lack of social auditing, diversity, and customer awareness. Originality/value – The article contributes by extending the application of multiple-criteria decision-making methods to CSR and evaluating the relative importance of the barriers. This study also offers empirical results that broaden the discussion on barriers to social responsibility, guiding managers and decision makers who lead CSR initiatives in organizations to understand which barriers should be overcome, and where managers should focus their effects to do so. Keywords - Analytic hierarchy process; Multicriteria decision making; CSR; Non-governmental organizations; Sustainable development.